Assessing carbon dioxide emission reduction potentials of improved manufacturing processes using multiregional input output frameworks. (1st October 2017) - Ward, Hauke; Burger, Mia; Chang, Ya-Ju; Fürstmann, Paul; Neugebauer, Sabrina; Radebach, Alexander; Sproesser, Gunther; Pittner, Andreas; Rethmeier, Michael; Uhlmann, Eckart; Steckel, Jan Christoph
Abstract: Evaluating innovative process technologies has become highly important within the last decades. As standard tools different Life Cycle Assessment methods have been established, which are continuously improved. While those are designed for evaluating single processes they run into difficulties when it comes to assessing environmental impacts of process innovations at macroeconomic level. In this paper we develop a multi-step evaluation framework building on multi regional input–output data that allows estimating macroeconomic impacts of new process technologies, considering the network characteristics of the global economy. Our procedure is as follows: i) we measure differences in material usage of process alternatives, ii) we identify where the standard processes are located within economic networks and virtually replace those by innovative process technologies, iii) we account for changes within economic systems and evaluate impacts on emissions. Within this paper we exemplarily apply the methodology to two recently developed innovative technologies: longitudinal large diameter steel pipe welding and turning of high-temperature resistant materials. While we find the macroeconomic impacts of very specific process innovations to be small, its conclusions can significantly differ from traditional process based approaches. Furthermore, information gained from the methodology provides relevant additional insights for decision makers extending the picture gained from traditional process life cycle assessment. Highlights: We develop a framework to assess impacts of process improvements in economies. We apply the novel method for innovative welding-, and turning processes. The developed methodology is contrasted with established LCA methods.